Experimental investigation on the micro-morphologies and growing process of methane hydrate formation in SDS solution. (1st June 2021) - Liu, Zhiming; Li, Yuxing; Wang, Wuchang; Song, Guangchun; Lu, Zhiyuan; Ning, Yuanxing; Liu, Shuai
Highlights: A high-speed camera was used for the micro-morphology of the formed hydrate. Five aggregation forms of hydrate particles were observed in liquid phase. Changes in energy barrier required for hydrate nucleation was discussed. Intuitively exhibited the microprobes of adherent formation and the way the liquid phase migrated. Mechanisms for the adherent growth and the different growth pattern were proposed. Abstract: The presence of surfactant could accelerate the hydrate formation dramatically, which is of great significance for the industrial application of the hydrate-based technologies. In this study, the micro-morphologies of the hydrate particles and the process of hydrate formed along the reactor wall was investigated using a high-speed camera. How the hydrate formed on the wall and the way the liquid phase migrated upward for the hydrate formation were intuitively exhibited, mechanisms for the adherent growth process and the different growth patterns were also proposed. It could be found that the hydrate particles formed in the Sodium Dodecyl Sulphate (SDS) solution was needle-shaped, and five aggregation forms were observed. The presence of SDS could make the critical size smaller and thus a lower energy barrier, both of which are facilitate to the hydrate nucleation and the further massive hydrate formation. When hydrate started to form on the wall, hydrate particles were accumulated and consolidated at the liquid–gas interface firstly, then stuck on the wall. Liquid phase could migrate upward through the porous hydrate under the capillary force for the further hydrate formation. In addition, the liquid film at the growth frontier and the condensate distributed on the wall were conducive to the moving of the growth frontier and the final hydrate formation. This work provides insights on the hydrate formation characteristics in SDS solution which facilitates to the rapid formation of hydrate and thereby promotes the industrial applications of the hydrate-based technologies.